Improvement of Seismic Performance of Beam-column Connection With Replaceable Drilled Attachment Parts - Vajdian, Mehdi; Parvari, Ali; Afzali, Mohammad (Periodica Polytechnica Civil Engineering, 2020)
Since beam-column connection plays a prominent role in steel structures, by designing and constructing it properly, the structure will behave better and safer. Numerous researches are carried out on steel connections, like Reduced Beam Section (RBS) and Drilled Flange Connection (DFC). Each connection has advantages and disadvantages. This study evaluates the effect of different connections on behavior of steel moment frames. The connections evaluated in this study are as follows: Connection with drilled attachment part, drilled connection with identical and variable diameter, beam connection with reduced flange. This connection contains one or two replaceable drilled parts that are mounted in connection place. The connection is modeled using the ABAQUS software. Finally, Finite Elements Modeling (FEM) is utilized to calculate the stiffness of each connection. According to the results of the newly introduced connection in terms of energy absorption and ductility is the best example and among the drilled models investigated in this study, drilled connection with variable diameter (proportional to diamond shape) which performed better in terms of behavior and performance than the other perforated models. Also, reduced flange connection ranks third in performance. In proposed connection the plastic hinge is formed at the attachment part of the connection that is replaceable, also there is little damage to the beams and columns, which is one of the main benefits of this connection.